Building the Resilient Indonesia’s Education in Pandemic Era: Lessons from Taiwan and the United States - Amja Manullang; Mohammad Ainul Maruf; Lalu Suprawesta (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The aim of the study is to analyze the measures from Taiwan and the United States that responded to the Covid-19 in high education institutions. The method that was conducted in this study is qualitative with a narrative review as a data technique. Data collected from reviewed the relevant literature that meets inclusion criteria as the primary object. The descriptive qualitative analysis technique was used. The result of this study concludes that some measures from Taiwan and United States can be matched according to the characteristic in Indonesia. These two countries provide several lessons in tackling the Covid-19 problem in the education sector by preventing the transmission since the beginning, taking mitigation steps to reduce the speed of the spread of the virus, applying clear regulations and guidelines in various fields of life including education, and have a sense of sensitivity to relaxed and tightened of regulations.